Re-examination of an improved Euro index under different market conditions. (2018) - Essayyad, Musa; Al-Titi, Omar
This paper updates Essayyad et al. (2011) research using multivariate tests to identify the most objective financial and economic factors that would improve the construction of the Euro index in order to improve measurement of movements in the currency markets. The data covers the expanded period from June 1999 to June 2015. The difference in the results of 2011 and 2016 studies can be attributed to the changes in the values of economic and financial variables due to economic/market collapse, natural disasters including droughts, escalating cost associated with the entanglement of the West in regional wars, and the subsequent recession that prevailed in the member countries of Organization for Economic Cooperation and Development (OECD). The aforementioned factors and the persistent increase in national debt have affected the exchange rate of the Euro.